Simultaneous imaging of fat crystallinity and crystal polymorphic types by Raman microspectroscopy. (1st April 2016) - Motoyama, Michiyo; Ando, Masahiro; Sasaki, Keisuke; Nakajima, Ikuyo; Chikuni, Koichi; Aikawa, Katsuhiro; Hamaguchi, Hiro-o
Highlights: Developed a method to visualize the crystalline states of fats quantitatively. Crystallinity and polymorphic type can be imaged out from Raman spectra together. Imaging of the major polymorphic types separately was possible. In a model fat system, β′ crystal polymorphs formed a colloidal-gel-like network. The emergence of β crystal polymorphs disturbed the continuity of the network. Abstract: The crystalline states of fats, i.e., the crystallinity and crystal polymorphic types, strongly influence their physical properties in fat-based foods. Imaging of fat crystalline states has thus been a subject of abiding interest, but conventional techniques cannot image crystallinity and polymorphic types all at once. This article demonstrates a new technique using Raman microspectroscopy for simultaneously imaging the crystallinity and polymorphic types of fats. The crystallinity and β′ crystal polymorph, which contribute to the hardness of fat-based food products, were quantitatively visualized in a model fat (porcine adipose tissue) by analyzing several key Raman bands. The emergence of the β crystal polymorph, which generally results in food product deterioration, was successfully imaged by analyzing the whole fingerprint regions of Raman spectra using multivariate curve resolution alternating least squares analysis. The results demonstrate that the crystalline states of fats can be nondestructively visualized and analyzed at the molecular level, in situ, without laborious sample pretreatments.